2022
DOI: 10.3390/cancers15010050
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy (SBRT) Plus Immune Checkpoint Inhibitors (ICI) in Hepatocellular Carcinoma and Cholangiocarcinoma

Abstract: The combination of stereotactic body radiation therapy (SBRT) plus immune checkpoint inhibitors (ICI) must be explored to treat advanced primary liver tumors such as hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). Limited retrospective reviews and case reports/series suggest this combination can be effective and safe in both cancer types. With ICIs moving into the first line (IMbrave 150, HIMALAYA, and TOPAZ-1) to manage these cancers, identifying a suitable population for this approach is challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Moreover, radiation therapy enhances antitumor T-cell response by stimulating effector phases, making it an excellent addition to PD-1 inhibitors 42 . Previous studies approved radiation plus PD-1 inhibitors therapy in HCC with PVTT 43,44 . Therefore, the combination therapy comprising lenvatinib, TACE, PD-1 inhibitor, and I 125 seed brachytherapy is expected to have a better therapeutic effect in the treatment of HCC, especially in patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, radiation therapy enhances antitumor T-cell response by stimulating effector phases, making it an excellent addition to PD-1 inhibitors 42 . Previous studies approved radiation plus PD-1 inhibitors therapy in HCC with PVTT 43,44 . Therefore, the combination therapy comprising lenvatinib, TACE, PD-1 inhibitor, and I 125 seed brachytherapy is expected to have a better therapeutic effect in the treatment of HCC, especially in patients with PVTT.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective reviews, case reports/series, and prospective data have looked at the association between SBRT and ICI in HCC specifically [ 60 , 61 ]. A prospective study analyzed safety of radiotherapy in patients with HCC followed by pembrolizumab and showed an acceptable toxicity [ 62 ].…”
Section: Combining Locoregional Treatments With Immune Checkpoint Inh...mentioning
confidence: 99%
“…Mounting evidence demonstrated that the combination of immunotherapy (included the combination of different immunosuppressors) and radiotherapy/chemotherapy/ablation may significantly promote the therapeutic efficacy in patients with unresectable or metastatic HCC (50)(51)(52)(53). Combination therapy may have better antitumor properties than monotherapy.…”
Section: Directions For Future Researchmentioning
confidence: 99%